COMMUNICATION RELATIONSHIP WITH NURSE PATIENT SATISFACTION THAT TREATED IN ROOM KANA GATOEL HOSPITAL - Darsini Darsini (Faculty of Nursing, Universitas Jember, 2016)
Medical technical skills alone are not sufficient to provide satisfactory service patient, it takes good communication between health workers or nurses with patients. Effective communication includes verbal and nonverbal communication effectively. The aim of this study knowing nurse communication relationship with the level of satisfaction of patients treated in the room Kana Gatoel Hospital Mojokerto. This type of research is an analytic correlation with the study design was cross-sectional design. Independent variables nurse communication. The populations are all patient populations Kana Gatoel Hospital Mojokerto as many as 54 patients. The sampling technique used is the type of probability sampling simple random sampling. This study was conducted on 13 July until 3 August 2015 in room Kana Gatoel Hospital Mojokerto. The instrument used was a questionnaire. Data is processing by means of editing, coding, scoring, and tabulating. Data were analyzed using chi square test. The results showed the majority of nurses is good communication as many as 29 respondents (60.4%) and the majority of patients satisfied with nurse communication as many as 32 respondents (66.7%). Based on Chi square test results obtained with the calculation of significant value p value = 0.000 while alfa = 0.05, which means there is a communication link nurse with patient satisfaction in Kana Gatoel Hospital Mojokerto. Patients say satisfied with verbal and nonverbal communication of nurses is good, it is because the approach and behavior of nurses were polite, and touch of the nurse implementations nursing care led to patient satisfaction. The health worker or nurse needs to quickly respond to any issues that arise in the nursing care services, especially verbal and nonverbal communication of nurses in giving satisfaction to the patient and seek alternative solutions.